The beneficial effect of the ethanolic extract Etlingera elatior fruit on IL-1ß and caspase-3 levels in sepsis model mice - Evi Nurhayatun,, Bambang Purwanto,, Soetrisno Soetrisno,, Dono Indarto,, Eti Poncorini,, Tatar Sumandjar, Febriola Hotmaida Sagala, Dalilah Salsabila Salma (Journal of Applied Pharmaceutical Science, 2023)
Etlingera elatior contains various active compounds with anti-inflammatory, antioxidant, and antibacterial effects. In sepsis, endothelial dysfunction can occur due to oxidative stress and hyperinflammation. This study evaluated the effect of E. elatior (EE) ethanolic extract in reducing IL-1ß and caspase-3 levels in sepsis model mice. Thirty-two Mus musculus mice (n = 32) were randomly distributed into four groups (n = 8). Induction of sepsis was performed through intraperitoneal injection of lipopolysaccharide (LPS) 0.3 mg/kgBW. Ethanol extract of EE 4.2 mg/20 g, p.o. was given 5 days before (EE-1), 5 days after (EE-2), and simultaneously during LPS induction (EE-3). ELISA was used to measure IL-1ß and caspase-3 levels. The ANOVA was performed to test the differences of each group. Mean levels of IL-1ß (p < 0.05) and caspase-3 (p < 0.05) differed in the control group with each intervention group. The EE significantly reduced levels of IL-1ß and caspase-3 (p < 0.05), with the best results being before LPS induction. This study provides that EE may have a role in averting endothelial dysfunction in sepsis by lowering levels of IL-1ß and caspase-3.